PENERAPAN MEDIA PEMBELAJARAN BERBASIS MARITIM UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS VIII SMP PADA MATERI PESAWAT SEDERHANA DI KECAMATAN SUNGAI APIT - Viranda, Nurrahmi Putri; Zulirfan, Zulirfan; M. Rahmad, M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Science process skills are the skills needed to acquire, develop, and apply concepts, laws, and theories of science, both in the form of mental skills, physical skills (manual) and social skills. This study aims to describe the learning outcomes of students' science process skills by applying maritime-based learning media. The research subjects were students of class VIII of SMPN 2 and SMPN 3 Sungai Apit. This type of research is a Quasi Experimental Design with a non equivalent control group design. This research instrument as many as 25 multiple choice questions. Data is collected by providing a test of science process skills to the subject. Data were analyzed descriptively to provide a picture of the results of learning the science process skills of students including the spread of abilities and increased ability on simple aircraft material. The results obtained were an increase in student ability shown by its N-Gain of 0.29 even though it was in the low category. Thus it can be concluded that the application of maritime-based learning media is effective for training the science process skills of Grade VIII students of SMP Negeri 2 and SMP Terror 3 Sungai Apit on simple aircraft material.Key Words: Maritime Based Media, Science Process Skills, Simple Aircraft.